2011
DOI: 10.1002/cbf.1731
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha is essential for the proliferation of prostatic smooth muscle cells stimulated by 17β‐estradiol and insulin‐like growth factor 1

Abstract: Estradiol (E₂) and its receptor estrogen receptor alpha (ERα) are implicated in the pathology of stromal-predominant benign prostatic hyperplasia (BPH). Insulin-like growth factor 1(IGF1) is produced primarily by stromal cells in the prostate. Recent study showed that E₂-mediated regulation of IGF1 in mouse uterus requires the DNA binding ability of ERα. However, the crosstalk between ERα and IGF1 in the prostate has not been addressed yet. Therefore, in this study we employed mouse prostatic smooth muscle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In fact, growth factors induce a periodic increase of cyclin D1 abundance by several mechanisms, which peaks during G1 [31,34]. Consequently, cyclin D1 levels are frequently used as a marker for proliferation, including investigations performed in prostate smooth muscle cells [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, growth factors induce a periodic increase of cyclin D1 abundance by several mechanisms, which peaks during G1 [31,34]. Consequently, cyclin D1 levels are frequently used as a marker for proliferation, including investigations performed in prostate smooth muscle cells [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…3). Previous studies have shown that E 2 can up-regulate IGF-I in smooth muscle cells and that this upregulation can increase these cells' proliferation (41). In addition to IGF, we have also observed that ER␣ can regulate EGF in other cell lines (Yeh, S., unpublished data).…”
Section: Er␣ Is Able To Regulate Growth and Collagen Through Igf/egf mentioning
confidence: 54%
“…These data suggest that besides contractibility, ERa may be involved in other epididymal functions. Indeed a recent study revealed that ERa is essential for proliferation of smooth muscle cells in the rat prostate [56]. Additionally, there is a growing body of evidence that factors arising from the interstitium may be important in stimulating epithelial cells by a paracrine action in diverse organs [49,56].…”
Section: Discussionmentioning
confidence: 99%